Sentinel lymph node scintigraphy in cutaneous melanoma using a planar calibration phantom filled with Tc-99m pertechnetate solution for body contouring - PEŞTEAN, CLAUDIU (Clujul Med, 2016)
BACKGROUND AND AIMS: Melanoma is a disease that has an increasing incidence worldwide. Sentinel lymph node scintigraphy is a diagnostic tool that offers important information regarding the localization of the sentinel lymph nodes offering important input data to establish a pertinent and personalized therapeutic strategy. The golden standard in body contouring for sentinel lymph node scintigraphy is to use a planar flood source of Cobalt-57 (Co-57) placed behind the patients, against the gamma camera. The purpose of the study was to determine the performance of the procedure using a flood calibration planar phantom filled with aqueous solution of Technetion-99m (Tc-99m) in comparison with the published data in literature where the gold standard was used. METHODS: The study was conducted in the Department of Nuclear Medicine of Oncology Institute “Prof. Dr. Ion Chiricuţă” Cluj-Napoca in 95 patients, 31 males and 64 females. The localization of the lesions was grouped by anatomical regions as follows: 23 on lower limbs, 17 on upper limbs, 45 on thorax and 10 on abdomen. The calibration flood phantom containing aqueous solution of Tc-99m pertechnetate was used as planar source to visualize the body contour of the patients for a proper anatomic localization of detected sentinel lymph nodes. The radiopharmaceutical uptake in sentinel lymph nodes has been recorded in serial images following peritumoral injection of 1 ml solution of Tc-99m albumin nanocolloids with an activity of 1 mCi (37 MBq). The used protocol consisted in early acquired planar images within 15 minutes post-injection and delayed images at 2–3 hours and when necessary, additional images at 6–7 hours. The acquisition matrix used was 128×128 pixels for an acquisition time of 5 – 7 minutes. The skin projection of the sentinel lymph nodes was marked on the skin and surgical removal of detected sentinel lymph nodes was performed the next day using a gamma probe for detection and measurements. RESULTS: The sentinel lymph nodes were detected in 92 cases and confirmed with the gamma probe during the surgical procedure. The localization of the lymph nodes was as follows: for the tumors localized on lower limb 23 lymph nodes were localized in inguinal region, for the tumors localized on upper limb, 17 lymph nodes were localized in axilla, for the tumors localized on the thorax, 40 lymph nodes were localized in axilla and 3 were localized in the inguinal region; for the tumors localized on the abdomen, 1 lymph node was localized in axilla and 8 lymph nodes was localized in inguinal region. Regarding the negative sentinel lymph node cases, 2 cases were registered for primarily lesions localized on thorax and 1 for a lesion localized on abdomen. According to histology, 26 cases revealed lymphatic metastatic invasion. Dose rates measured at 1m from the calibrator phantom had an average value of 3.46 μSv/h (SD 0.19) and at 1.4m, the value was 2.57 μSv/h (SD 0.22). Dose rates measured at the same distances from the Co-57 planar flood source had a average values of 32.5μSv/h (SD 0.11) respectively 24.1 μSv/h (SD 0.14). CONCLUSION: The planar calibration flood phantom is an effective tool for body contouring in sentinel lymph node scintigraphy and offers accurate anatomical information to efficiently localize the detected sentinel lymph nodes in melanoma, being for the first time used and mentioned as a pertinent alternative in our department.